2014
DOI: 10.1113/jphysiol.2014.275438
|View full text |Cite
|
Sign up to set email alerts
|

Spinal μ‐opioid receptor‐sensitive lower limb muscle afferents determine corticospinal responsiveness and promote central fatigue in upper limb muscle

Abstract: Key pointsr We aimed to elucidate the role of group III/IV locomotor muscle afferents in the development of central fatigue and the responsiveness of the corticospinal tract in relation to an unexercised arm muscle.r Intrathecal fentanyl, a μ-opioid receptor agonist, was employed to attenuate afferent feedback from the leg muscles during intense cycling exercise characterized by either no or severe peripheral locomotor muscle fatigue.r In the absence of locomotor muscle fatigue, group III/IV-mediated leg affer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
137
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(153 citation statements)
references
References 32 publications
15
137
1
Order By: Relevance
“…The similar reduction in voluntary activation after CYC and ARM-CYC indicates that central fatigue developed more quickly in ARM-CYC, possibly due to a "spill-over" of central fatigue from the exercised upper body muscles to the leg locomotor muscles. In support, it was recently demonstrated that fatiguing leg cycling exercise resulted in a "spillover" of central fatigue (i.e., reduced voluntary activation) to the remote unexercised elbow flexors (69). This effect was attributed to inhibitory group III/IV muscle afferent feedback originating in fatigued leg muscle, since attenuating this feedback using intrathecal fentanyl abolished the decline in voluntary activation of the elbow flexors.…”
Section: Discussionmentioning
confidence: 93%
“…The similar reduction in voluntary activation after CYC and ARM-CYC indicates that central fatigue developed more quickly in ARM-CYC, possibly due to a "spill-over" of central fatigue from the exercised upper body muscles to the leg locomotor muscles. In support, it was recently demonstrated that fatiguing leg cycling exercise resulted in a "spillover" of central fatigue (i.e., reduced voluntary activation) to the remote unexercised elbow flexors (69). This effect was attributed to inhibitory group III/IV muscle afferent feedback originating in fatigued leg muscle, since attenuating this feedback using intrathecal fentanyl abolished the decline in voluntary activation of the elbow flexors.…”
Section: Discussionmentioning
confidence: 93%
“…Based on this observation, the extent to which central motor drive increases during aerobic cycling can influence the interpretation of exercise-induced net changes in corticomotoneuronal excitability. Specifically, the inhibitory effect of locomotor muscle fatigue on corticomotoneuronal excitability (31) can, at least up to a certain point, be masked by the facilitating effect of an increase in central motor drive. Thus during strenuous constant-load aerobic leg exercise characterized by the development of peripheral fatigue and associated progressive increases in central motor drive (4), the net corticomotoneuronal excitability depends on the balance between the facilitating effects of an increase in central motor drive and the potentially inhibitory effects of fatigue (31).…”
Section: Locomotor Exercisementioning
confidence: 99%
“…On the other hand, Group III/IV muscle afferent feedback associated with intramuscular metabolic perturbation has been suggested to have an inhibitory effect on the central nervous system (i.e., central fatigue), limiting the output of spinal motoneurons during exhaustive locomotor exercise (Amann et al 2013;Amann et al 2015;Hilty et al 2011;Sidhu et al 2014). Moreover, it has been suggested that decrease in the output from spinal motoneurons is attributed to the inhibitory effect of group III/IV muscle afferents on voluntary descending drive 'upstream' of the motor cortex (Taylor et al, 2006) and/or an afferent-mediated depression of excitability of the corticospinal tract (Hilty et al 2011, Martin et al 2006Martin et al 2008, Sidhu et al 2014. In the present study, MEP was significantly lower in IE 2nd than in IE 1st , while M max was similar in the two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that reductions in the output from spinal motoneurons are attributed to the inhibitory effect of group III/IV muscle afferents on excitability of the corticospinal tract consisting of the motor cortex and spinal motoneurons (Hilty et al 2011;Martin et al 2006;Sidhu et al 2014). In this kind of situation, there is a possibility that activation of upstream regions of the motor cortex might be involved in the generation of a greater effort sense and consequently an increase in ventilation in order to maintain a required power output during IE (Amann et al 2013).…”
Section: Introductionmentioning
confidence: 99%